Differences in treatment for Alzheimer's disease between urban and rural areas in China - Li, Bei; Liu, Dejun; Wan, Qiaoqin; Sheng, Can; Wang, Xiting; Leng, Fangda; Peng, Qing; Wang, Ting; Du, Ailian; Zhu, Feiqi; Mima, Dunzhu; Wang, Huali; et al. (Frontiers in Neurology, 2022)
Introduction: In China, the increasing number of people with Alzheimer's disease (AD) poses a great challenge to families and the country. Economic and cultural differences cause a urban-rural gap in medical resources. This multicenter survey aimed to investigate the real-world practice of disease treatment among people with AD. Methods: People with AD and their caregivers from 30 provincial regions in mainland China were enrolled from October 2020 to December 2020 to be surveyed for their treatment experience. Logistic regression was used to explore the factors that influence medication adherence in all areas, urban areas, and rural areas. Results: In this survey, 1427 participants came from urban areas, and 539 participants came from rural areas. Patients in urban areas were older (mean age 74 vs. 70, p = 0.001), less frequently had mild AD (36.0% vs. 52.1%, p < 0.001), and more often were cared for at professional institutions (8.8% vs. 3.2%, p < 0.001). In terms of pharmacotherapy, 77.8% of people accepted taking lifelong medication, whereas 61.3% of patients insisted on taking medications. Although 72.0% of rural people believed in taking lifelong medication, only 30.0% adhered to drug use. The major factors that influenced medication adherence for all patients with AD were regional distribution (p < 0.001, OR = 6.18, 95% CI: 4.93-7.74) and family earnings (p = 0.003, OR = 1.22, 95% CI: 1.07-1.38). In rural areas, family earnings (p = 0.008, OR = 1.44, 95% CI: 1.10-1.89) and severity of AD (p = 0.033, OR = 1.31, 95% CI: 1.02-1.68) were the main factors. Family earnings (p = 0.038, OR = 1.16, 95% CI: 1.01-1.34) was the only factor among urban areas. Among all nonpharmaceutical activities except for cognitive intervention, the participation rates of rural patients were significantly higher than those of urban patients (p < 0.05). Conclusion: Although national progress has been made in the public awareness of disease treatment, adequate diagnosis and medication adherence need to be prompted, especially in rural areas. Furthermore, lifelong treatment should be improved based on regional characteristics through the joint efforts of the government, health workers, and social volunteers.